Legal Reform Project, Access to Justice and Gender Equity in Indonesia - Alfitri, Alfitri (UI Scholars Hub, 2012)
This article is to discuss the impact of legal reform project between Indonesian and Australian government in assisting women, the poor and those living in remote areas to access the judiciary in Indonesia. Through the program access to the Religious Courts for divorce cases, for example, women are able to document their role as female heads of household. The document is necessary to facilitate access to the Indonesian Government pro-poor programs such as cash transfers, free health treatment, subsidized rice or enrolment of children at state schools. This article argues that the access to justice program in Religious Courts has positive impacts on gender equity development in Indonesia. This argument is based on AmartyaSen’s conception of development that must go well beyond “the accumulation of wealth and the growth of gross national product and other income-related variables.” Thus, the process of development is really all about removing “the unfreedoms” from which the members of society may suffer. Access to the Religious Courts program for women, the poor and marginalized groups, which was initially supported by the Australian Government through its agencies, has “opened” Indonesian government mind on how to address obstacles in removing “the unfreedoms” of gender discrimination caused by the family laws.